Circuit resistance training strategy on maximal strength, rate of force development and power: A random model meta-analysis - Kahraman, Yeliz; Hocalar, Aykut (Journal Sport Area, 2024)
Backround Problems: Circuit resistance training is a type of strength and power training mode according to short-term strength, rate of force development, and power strategy; however, priority maximises performance outcomes and is not used on trained and untrained resistance populations. Research Objectives: Increased performance on developing high-intensity resistance sessions and short time intervals was investigated with systematic review and meta-analysis methodology. This meta-analysis methodologic approach aimed to report popular circuit resistance training on maximal strength, rate of force development, and power able to short-time interval set-up micro-periodization. Methods: By following this way, a high-intensity resistance combination short-time interval strategy was provided between 2008 and 2023. A study using keywords of circuit resistance training, dynamic strength, explosive power, and rate of force development was conducted to explore SportDiscus, PubMed, and the and the Web of Science databases investigated in a random model meta-analysis. Findings and Results: Exploration of circuit resistance training contributed to clarifying maximise strength and power performance under probable report outcomes detected to analysis of metadologic quality risk of bias, effect size, and mean difference. Conclusion: In conclusion, circuit resistance training strategy resulted in maximising strength and power regimes, but sufficient research has not yet been carried out as a proper periodic session adapted to detect rate of force development and power combination in the literature. In addition, circuit resistance training strategic approach may be re-performed to plan strength and power.